Preparation And Characterization Of Poly(3-Hydroxybutyrate-Co-3- Hydroxyhexanoate) Reinforced Kenaf Fibre - Lee, Joyyi (2017)
Polyhydroxyalkanoate (PHA) is an advantageous polymeric material due to environmental friendliness but its mechanical properties limits its potential in material selection. Green composites, produced from renewable polymers such as thermoplastic PHA and natural fibres, are possible ways to solve this shortcoming. It can potentially substitute non-renewable synthetic materials in composite manufacturing sector. The polymer component of the composite, poly(3- hydroxybutyrate-co-3-hydroxyhexanoate) [P(3HB-co-3HHx)] with 3HHx monomer fraction of approximately 20 mol%, was biosynthesized by fermentation using used cooking oil as the sole carbon source. Subsequently, bulk quantity ofP(3HB-co-3HHx) was recovered using solvent-free novel biological recovery method with yellow mealworms (Tenebrio molitor) and followed by further purification with water containing strong anionic detergent. P(3HB-co-3HHx) showed slightly better thermal stability than its solvent extracted derivative with the removal of inorganic compounds during the purification process.